Synthesis and structural studies of a lanthanide complex of a calix[4]arene tris-amide - Ogden, Mark; Skelton, B.; White, A. (Elsevier SAS, 2005)
The coordination chemistry of amide-substituted calixarenes is reviewed. The synthesis of a gadolinium complex of a trisamide calix[4]arene is described, involving the reaction of 5,11,17,23-tetra-tert-butyl-24-hydroxy-26,27,28-tris(diethylcarbamoylmethoxy) calix[4]arene (L) with gadolinium picrate dodecahydrate. Structural studies demonstrated that the complex can be formulated as [(pic-O)Gd{(L H)(EtOH)}](pic)2 EtOH.